Differently Charged P (VDF-TrFE) Membranes Influence Osteogenesis Through Differential Immunomodulatory Function of Macrophages - Zhu, Peijun; Lai, Chunhua; Cheng, Mingwei; He, Yiheng; Xu, Yan; Chen, Jiahao; Zhou, Zhengnan; Li, Ping; Xu, Shulan (Frontiers in Materials, 2022)
A biomaterial-mediated immune response is a critical factor to determine the cell fate as well as the tissue-regenerative outcome. Although piezoelectric-membranes have attracted considerable interest in the field of guided bone regeneration thanks to their biomimetic electroactivity, the influence of their different surface-charge polarities on the immune-osteogenic microenvironment remains obscure. The present study aimed at investigating the interaction between piezoelectric poly (vinylidene fluoridetrifluoroethylene) [P (VDF-TrFE)] membranes with different surface polarities (negative or positive) and macrophage response, as well as their subsequent influence on osteogenesis from an immunomodulating perspective. Specifically, the morphology, wettability, crystal phase, piezoelectric performance, and surface potential of the synthetic P (VDF-TrFE) samples were systematically characterized. In addition, RAW 264.7 macrophages were seeded onto differently charged P (VDF-TrFE) surfaces, and the culture supernatants were used to supplement cultures of rat bone marrow mesenchymal stem cells (rBMSCs) on the corresponding P (VDF-TrFE) surfaces. Our results revealed that oppositely charged surfaces had different abilities in modulating the macrophage-immune-osteogenic microenvironment. Negatively charged P (VDF-TrFE), characterized by the highest macrophage elongation effect, induced a switch in the phenotype of macrophages from M0 (inactivated) to M2 (anti-inflammatory), thus promoting the osteogenic differentiation of rBMSCs by releasing anti-inflammatory cytokine IL-10. Interestingly, positively charged P (VDF-TrFE) possessed pro-inflammatory properties to induce an M1 (pro-inflammatory) macrophage-dominated reaction, without compromising the subsequent osteogenesis as expected. In conclusion, these findings highlighted the distinct modulatory effect of piezoelectric-P (VDF-TrFE) membranes on the macrophage phenotype, inflammatory reaction, and consequent immune-osteogenic microenvironment depending on their surface-charge polarity. This study provides significant insight into the design of effective immunoregulatory materials for the guided bone regeneration application.